646 Publication Speed Across Neurosurgical Journals: A Bibliometric Analysis. (April 2023) - Hanna Jubran, Jubran; Scherschinski, Lea; Park, Marian; Rhodenhiser, Emmajane; Benner, Dimitri; Ibrahim, Sufyan; Karahalios, Katherine; Singh, Rohin; Maher Hulou, M.; Graffeo, Christopher S.; Lawton, Michael T.
Abstract : INTRODUCTION: Many factors influence an author's choice for journal submission, including the journal impact factor and publication speed. These bibliometric data points, amongst others, have not yet been assessed in neurosurgical research. METHODS: Eight neurosurgical journals were analyzed for original articles, collected via randomized sampling per issue per year from 2016-2020. Publication speed data was gathered from published articles. Journal Impact Factors were gathered using Clarivate Journal Citation Reports. Spearman's correlation analysis was used to analyze the findings. RESULTS: A total of 1617 original articles and systematic reviews across 8 neurosurgical journals were reviewed. The mean (standard deviation; SD, range) time from submission to print publication (SP) in neurosurgery journals is 344 (190) days, while the submission to acceptance (SA) time is 130 (104) days, acceptance to online print (AO) time is 76 (61) days, and the online publication to print publication (OP) is 137 (114) days. Most articles were from authors from the United States (n = 833; 52%), with the second and third highest contributions coming from China (n = 100; 6%) and Japan (n = 83, 5%) respectively. The top three neurosurgical topics published were spine (n = 417; 26%), vascular (n = 316; 20%) and oncology (n = 275; 17%). There were significant correlations across all determinants of publication speed and journal Impact Factors (SP: r = 0.457, SA: r = 0.204, AO: 0.481, OP: 0.317, p < 0.001). CONCLUSIONS: Neurosurgical journal publication speeds vary between journals and are significantly correlated with the journal's impact factor. The majority of neurosurgical research in the past five years has been focused in spine, vascular, and oncology fields and has originated from the United States. The information on individual journals could serve as a guide for publishing neurosurgeons to determine the appropriate journal for submission.